2003
DOI: 10.1007/s00592-003-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

The application of body cell mass index for studying muscle mass changes in health and disease conditions

Abstract: Body mass index (BMI) fails to detect altered nutritional state in the presence of overweight or obesity, since malnutrition can be present and masked by the abnormal amount of fat mass. Measuring body cell mass (BCM) contents for the evaluation of muscle mass and protein tissue states is well accepted. The aim of the present study was to apply body cell mass index (BCMI) to monitor the muscular mass changes of male and female Olympic athletes, renal dialysis patients, and anorexia nervosa patients in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 9 publications
3
33
0
2
Order By: Relevance
“…between 20 and 30), there is a great variability in BCMI (i.e. between 5 and 19 kg/m 2 ), which means that these subjects may appear overweight on the basis of BMI, but in fact those who have lower BCMI values are malnourished (Talluri et al 2003). This observation agrees with our study as the women with CVD had significantly higher BMI values and significantly lower BCMI values in comparison with women without CVD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…between 20 and 30), there is a great variability in BCMI (i.e. between 5 and 19 kg/m 2 ), which means that these subjects may appear overweight on the basis of BMI, but in fact those who have lower BCMI values are malnourished (Talluri et al 2003). This observation agrees with our study as the women with CVD had significantly higher BMI values and significantly lower BCMI values in comparison with women without CVD.…”
Section: Discussionsupporting
confidence: 90%
“…The BCMI has been shown to be more sensitive to changes in protein status and lean tissue compared to BMI (Talluri et al 2003). Further, it has been observed that for subjects with normal or high BMI values (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were performed on the dominant side, while participants lied supine on an examination table with their limbs abducted away from the trunk. Four gel electrodes were attached on defined anatomical positions on the hand, wrist, ankle and foot (Talluri et al, 2003;Kyle et al, 2004a, b). The BIA measurements were performed using an Akern BIA (Florence, Italy) and Littmann 2325VP adhesive electrodes (3M, St Paul, MN, USA).…”
Section: Body Composition Analysismentioning
confidence: 99%
“…According to Talluri et al (2003) the index of metabolically active cells (BCMI, Body Cell Mass Index; 11.9 to 12.1) corresponds to the health recommendations for women. Minimum values found in our groups meet these recommendations.…”
Section: Discussionmentioning
confidence: 99%